ISSUES OF USING EDUCATIONAL TECHNOLOGIES IN TEACHING THE BASIC RULES OF COMBINATORICS AND ELEMENTS OF COMBINATORICS TO VOCATIONAL SCHOOL STUDENTS - Kasimova Nilufarkhan Gafurovna (Лучшие интеллектуальные исследования, 2024)
Abstract: In this scientific work, the topical issues of interactive organization of the lesson on the subject of "Basic rules of combinatorics and elements of combinatorics" were discussed in vocational education institutions. The work covers the organization of practical training and independent work on the topic. Some reforms in the professional education system were also discussed.